Immunogenetic characteristics of LADA - Tatiana Vasil'evna Nikonova; Pavel Vasil'evich Apanovich; Elena Vladimirovna Pekareva; Vera Anatol'evna Gorelysheva; Svetlana Mikhailovna Stepanova; Yulia Vladimirovna Tishina; Sergey Alexandrovich Prokof'ev; Alexander Vasil'evich Karpukhin (Сахарный диабет, 2011)
Latent autoimmune diabetes of adults (LADA) is a variant of autoimmune diabetes mellitus. Its clinical feature not typical for classical DM1 despitethe presence of positive autoantibodies is characterized by the low rate of autoimmune destruction that accounts for the late development of insulindependence. Similar to classical DM1, LADA is associated with the loss of immune tolerance to autoantibodies. However, the quantitative andfunctional activity of Treg as key regulators of the immune response and main agents of immune tolerance remain as poorly known as their relationshipwith characteristics of apoptosis.Aim. To elucidate qualitative and functional changes at the level of immunity regulation in patients with LADA of different duration and theirrelationships with characteristics of apoptosis, immunological and genetic markers. Materials and methods. The study included 64 patients (45 men and 19 women) with LADA and 56 control subjects. The methods included HLAgenotyping, detection of autoantibodies against GAD, insulin, tyrosine phosphatase, islet cell antigens, composition of CD3+, CD4+, CD38+, HLADR+, CD25+, CD+25+, CD95, CD95L lymphocyte subpopulations, FoxP3 and C-peptide expression, HbA1c levels. Results. FoxP3 expression at the onset of LADA was similar to that in control subjects while the relative amount of CD425+high T-lymphocytes increased.In contrast to DM1, FoxP3 expression began to decrease 6-12 months after the onset of LADA when the amount of CD425+high T-lymphocytes loweredto become normal with the progress of the disease. Within 1-5 years after the onset of LADA, FoxP3 expression became normal again but significantlyincreased when its duration exceeded 5 years. Expression of apoptosis markers (CD95 and CD95L) on lymphocytes and of their soluble forms in allLADA patients was comparable with control. Conclusion. We for the first time determined intensity of FoxP3 expression and the amount of CD425+high T-lymphocytes in patients with differentduration of LADA. FoxP3 expression varies periodically while functional deficit of Treg is delayed and appears to be compensated by a rise in theirnumber. Increased population of Treg within 6 months after the onset of LADA may reflect their regulatory role (suppression of autoimmunity)accounting for the gradual development of the disease.